2022
DOI: 10.1002/adom.202102388
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Material, Near‐Infrared Selective Absorber Based on Refractive Index‐Tunable Tamm Plasmon Structure

Abstract: efficient photonic applications such as near infrared spectra analysis, [1] telecommunications, [2] biomedical and chemical sensing. [3] Rapidly advancing plasmonics are of particular interest, along with their selective light-trapping with strongly localized photon energy, surface plasmons (SPs) have attracted attention due to their potential applications in medicine and chemistry, [4,5] as well as optical switching and near-field photonics. [6][7][8] However, many studies still rely on the Kretschmann-Raethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…However, the fabrication processes of such nanostructured absorbers usually require high precision and costly lithography techniques such as electron-beam lithography, which makes them difficult for massive industrial manufacturing and hence limiting their practical applications. An alternative approach for achieving perfect absorbers involves the use of multilayer thin-film stacks; [21][22][23] however, in traditional multilayer thin-film structure designs, each thin film features one quarter wavelength thickness, it results in the structure sensitive to the incident angles or polarizations, limited the applications in some specific situations.…”
mentioning
confidence: 99%
“…However, the fabrication processes of such nanostructured absorbers usually require high precision and costly lithography techniques such as electron-beam lithography, which makes them difficult for massive industrial manufacturing and hence limiting their practical applications. An alternative approach for achieving perfect absorbers involves the use of multilayer thin-film stacks; [21][22][23] however, in traditional multilayer thin-film structure designs, each thin film features one quarter wavelength thickness, it results in the structure sensitive to the incident angles or polarizations, limited the applications in some specific situations.…”
mentioning
confidence: 99%
“…Bikbaev et al [137] have theoretically demonstrated a narrowband perfect absorber exploiting TPP localized at the interface between a 1DPC and a nanocomposite with near-zero effective permittivity. Recently, Kim et al [138] have proposed a TP structure made of single material whose refractive index is tailored through porosity and prepared using glancing angle deposition technique. The single material TP structure shows near-unity absorption of ~99% with Q-factor of ~45 at λ=700 nm.…”
Section: Perfect Absorbersmentioning
confidence: 99%
“…Another significant advantage of TMM structures is that they can be fabricated by cost-competitive, fully scalable nanofabrication methods. This in turn provides high versatility to create new hybrid structures that can harness TMM resonances at specific wavelengths by judiciously engineering the properties and characteristics of the metal film and the underlying dielectric structure. , Structures supporting TMM modes have demonstrated versatility in different photonic fields such as lasers, photodetectors, thermal emitters, and sensors. A variety of materials have been explored as the plasmonic and photonic components of TMM systems, including magneto–photonic crystals (PCs), semiconductors and all-dielectric PCs, and epsilon-near-zero platforms . One dimensional PCs are the most frequently used photonic component due to their ease of design and fabrication, with the most widespread structure being a distributed Bragg reflector (DBR).…”
Section: Introductionmentioning
confidence: 99%